2009
DOI: 10.1111/j.1468-1331.2009.02723.x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin B increases mouth opening in patients with spastic trismus

Abstract: Botulinum toxin serotype B injections into the masseter muscles effectively reduce hypertonia and provide for better mouth opening, thereby contributing to a positive and desired clinical goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…This is similar to the incidence of AEs found in two other studies involving children with CP receiving BoNT-B, 3,13 slightly lower than that reported for adults with cervical dystonia, 69 and much greater than that reported for children having BoNT-A injections. 11,12 Interestingly, there was no significant difference with regard to experiencing an AE and the presence or the absence of a clinical response to the injections.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is similar to the incidence of AEs found in two other studies involving children with CP receiving BoNT-B, 3,13 slightly lower than that reported for adults with cervical dystonia, 69 and much greater than that reported for children having BoNT-A injections. 11,12 Interestingly, there was no significant difference with regard to experiencing an AE and the presence or the absence of a clinical response to the injections.…”
Section: Discussionsupporting
confidence: 87%
“…In adults with cervical dystonia, the increased incidence of adverse effects (AEs) ranges from 0% to 89%, with most studies showing the incidence 69 to be greater than 50%. Currently, all botulinum toxins approved by the United States Food and Drug Administration have a boxed warning regarding the potential for spread to noninjected muscles, based on AE reports, including one randomized study involving BoNT-A use in children with CP that reported a death.…”
mentioning
confidence: 99%
“…It is therefore not surprising that the results from GAS are more sensitive and clinically relevant when compared with those of psychometric measures. This view is supported by studies in other fields, which have employed goal attainment measures to identify positive clinical outcomes for patients (Fietzek et al ., ). A potential criticism of these findings is that if caregivers and patients have low expectations of treatment, then the goals set would be too easy to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have used botulinum toxin for spastic trismus after stroke in the cerebral hemisphere, traumatic brain injury, and hypoxic encephalopathy with relatively successful results. In a placebo-controlled randomized study, they used 2500 units of botulinum toxin type B in each masseter muscle for improvement of trismus after brain damage, and showed significantly increased mouth opening after botulinum toxin injection compared with placebo treatment 4. Another report used 75 units of botulinum toxin A to each masseter muscle to improve PEG placement in 18 patients with masseter hyperactivity caused by TBI and ischemic stroke 5.…”
Section: Discussionmentioning
confidence: 99%